Economic Outcomes of Youth not in Education, Employment or Training (NEET) - Anton Samoilenko; Kristie Carter (New Zealand Government, The Treasury, 2015)
The paper examines the outcomes of youth not in education, employment or training (NEET) up to four years after the initial long-term spell of NEET. The paper covers outcomes of NEETs in relation to benefit receipt, education, employment and future inactivity. These outcomes are compared across NEETs and a control group of non-NEETs. Propensity Score Matching is used to control for observed characteristics of NEETs and controls to ensure that outcomes are not driven by underlying differences in specific characteristics. The paper finds that individuals who experience a long-term spell of NEET in their youth experience relatively poorer outcomes than their control group peers after the first two years. Long-term NEETs are less likely to be employed, are more likely to be inactive and/or receiving a benefit. There are no differences in the rates of study. The differences in outcomes between NEETs and the control group are reduced after four years.
Keywords: C1; I24; I3; 330; youth; NEET; outcomes; education; employment; welfare; Propensity Score Matching; Jugendarbeitslosigkeit; Junge Arbeitskräfte; Weiterbildung; Beschäftigungsfähigkeit; Arbeitsmarktintegration; Beschäftigungseffekt; Neuseeland